2021
DOI: 10.36072/wp.20
|View full text |Cite
|
Sign up to set email alerts
|

Gender equity and reduction of post-harvest losses in agricultural value chains

Abstract: The Global Alliance for Improved Nutrition (GAIN) is a Swiss-based foundation launched at the UN in 2002 to tackle the human suffering caused by malnutrition. Working with governments, businesses and civil society, we aim to transform food systems so that they deliver more nutritious food for all people, especially the most vulnerable. Recommended citationNordhagen, S. Gender equity and reduction of post-harvest losses in agricultural value chains. Global Alliance for Improved Nutrition Working Paper #20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…In the study areas, storage of ware potato is mainly done by women often for household food consumption, which could explain their higher intentions to store potato. This finding is consistent with Nordhagen (2021), who found that women are more involved in storage decisions, especially in food value chains. This finding points to the importance of being gender intentional when designing potato storage interventions that seek to change previously gendered practices (Mudege et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…In the study areas, storage of ware potato is mainly done by women often for household food consumption, which could explain their higher intentions to store potato. This finding is consistent with Nordhagen (2021), who found that women are more involved in storage decisions, especially in food value chains. This finding points to the importance of being gender intentional when designing potato storage interventions that seek to change previously gendered practices (Mudege et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Additionally, more work is needed on gender and food loss. Women account for approximately half of the workforce in aquatic food value chains 5 , and it has been recognized that gender and gender equity affect loss [42][43][44] .…”
Section: Articlementioning
confidence: 99%
“…In aquaculture, the highest rates of quality loss were tilapia in China and Bangladesh (14% and l1% loss, respectively), shrimp in Bangladesh and Vietnam (9% each), and freshwater species (carps, rui, catla) in Bangladesh (9%). In LMICs, a large share of losses occur in post-harvest processing where women play a large role; and it has been recognized that gender and gender equity affect loss 42 . In Zambia, researchers found a large gender gap in post-harvest losses (3 times greater losses of sh among female than male processors) and recommend improving processing technology and addressing unequal gender relations to reduce loss and promote food security 43 .…”
Section: Quality Lossmentioning
confidence: 99%